PENGARUH ASPEK IMPLEMENTASI DAN ASPEK MANFAAT DALAM PELAKSANAAN ANGGARAN TERHADAP NILAI KINERJA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA - Rukmi Juwita; Resya Ayu P.A.Y Syamara (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2017)
Abstract: Bureau of Finance and the State Property in the National Land Agency of the Republic of Indonesia is a unit that includes most of the financial activities of BPN. In the assessment the value performance of BPN can be provided by using Aspect of Implementation and Aspect of Benefits in the implementation of the budget. Therefore, with reference to the Ministry of Finance Regulation No. 249 / PMK.02 / 2011, researchers conducted a study of the influence of the Aspect of Implementation and Aspect of Benefits (Independent Variable/X2) of the Performance Value (Dependent Variable/Y) of BPN. The method used in this research is associative method. The result is the value of T for 16,318 of Implementation Aspects and 244 of Benefits Aspects. With the significant benefits of 0,000 for both. While the F value of the research is 1223.233. From these results it can be concluded that the implementation aspect and the aspect of benefits have a positive and significant effect partially to Value Performance. Aspects of Implementation and Benefits aspects together have a positive and significant effect on the performance value. Keywords: Implementation Aspects, Benefits Aspects, Performance Value